2018
DOI: 10.1038/s41366-018-0160-8
|View full text |Cite
|
Sign up to set email alerts
|

Causal relationships between adiposity and childhood asthma: bi-directional Mendelian Randomization analysis

Abstract: High adiposity may lead to asthma, whereas the effects of asthma on adiposity accumulation are likely to be small.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(43 citation statements)
references
References 32 publications
5
35
0
3
Order By: Relevance
“…As highlighted above, a significant genetic correlation might arise because of a causal effect of these risk factors on asthma risk. [83][84][85][86] At least for obesity, such a causal effect does not appear to extend to other allergies, 87 which could potentially explain the difference in genetic correlation between AOA and COA.…”
Section: Discussionmentioning
confidence: 99%
“…As highlighted above, a significant genetic correlation might arise because of a causal effect of these risk factors on asthma risk. [83][84][85][86] At least for obesity, such a causal effect does not appear to extend to other allergies, 87 which could potentially explain the difference in genetic correlation between AOA and COA.…”
Section: Discussionmentioning
confidence: 99%
“…These findings highlighted the imperative to monitor BMI and control weight routinely among the asthmatic children, even in regions exhibiting a relatively low prevalence of asthma and obesity, to combat comorbidity of asthma and obesity. However, it is worth noting that the only longitudinal study [13] in China investigating the causal relationship between asthma and adiposity only showed a small effect of asthma on adiposity accumulation among children aged 9-13 years, which is inadequate to clarify the underlying causality. Thus, more longitudinal data from diverse populations will be necessary to elucidate this conundrum.…”
Section: Discussionmentioning
confidence: 99%
“…The few longitudinal studies showed that asthma was associated with higher risks of subsequent weight gain and/or obesity in children [10][11][12]. In contrast, results from other studies did not support the effect of asthma on adiposity accumulation [13] or overweight/obesity development [14]. Additionally, it is worth noting that the vast majority of existing evidence was based on data from the US [7,8,10,11] or European countries [5,6,12], where the prevalence of asthma and obesity are relatively high [15,16], conferring an uncertainty when applied to other populations.…”
Section: Introductionmentioning
confidence: 93%
See 1 more Smart Citation
“…Chen et al (43) carried out a bidirectional MR analysis of the direction of causation between obesity and childhood asthma in Taiwan. While the obesity genetic risk score was a significant predictor of asthma, the asthma genetic risk score did not predict obesity.…”
Section: Mendelian Randomization Studiesmentioning
confidence: 99%